Intraoral Potentially Malignant Disorders in a Brazilian Oral Pathology Service: Epidemiological, Clinical, and Histopathological Findings. (1st March 2018) - Mello, Fernanda Weber; Melo, Gilberto; Meurer, Maria Inês; Rivero, Elena Riet Correa
Abstract : The aim of this study was to investigate the characteristics of individuals with intraoral potentially malignant disorders (IOPMD) in an oral pathology service in Brazil. Cases were screened based on clinical diagnosis of leukoplakia (LKP), erythroleukoplakia (ELKP), and erythroplakia (EP). Clinical data and information regarding associated factors were gathered from biopsy reports. Histological diagnoses were collected from histopathological records. Among 208 IOPMD cases, 84.13% involved LKP; 11.1%, ELKP; and 4.8%, EP. The most affected sites were the gingiva and buccal mucosa. Histologically, epithelial dysplasia was present in 66.8% of the lesions, acanthosis and hyperkeratosis without epithelial dysplasia were present in 27.9%, and squamous cell carcinoma was present in 2.9%. Most patients were males, fair-skinned, with mean age of 53.4 years. Chronic smokers represented 73% of subjects, of which 30% also consumed alcohol. Smokers and drinkers were mostly males( p < 0.001 ) . EP and ELKP represented histologically more severe degrees of epithelial dysplasia than LKP( p < 0.001 ) . In conclusion, individuals with IOPMD were more frequently fair-skinned men in the sixth decade of life, with smoking habit. Special attention is required to clinical diagnoses of ELKP and EP since the prevalence of severe epithelial dysplasia, in situ carcinoma, and squamous cell carcinoma is higher than in LKP.